PERANCANGAN ENVIRONMENTAL GRAPHIC DESIGN DESA WISATA NAGREG KENDAN KABUPATEN BANDUNG - Waren, Aryna; Denny Nugraha, Novian; Soedewi, Sri (eProceedings of Art & Design, 2024)
With a wide range of potential destinations, Nagreg Kendan Village is includedin one of the tourist village programsHowever, due to the fact that Nagreg Kendan is anew community or the outcome of Nagreg community's land development, this NagregCounty Village still lacks the means and means of information, such as hints or directionsfor visitors, so that visitors can be lost and less comfortable when arriving at existingdestinations. For that, this research and design are useful to create a solution that isenvironmental graphic design, signage, and wayfinding for Nagreg Tourism Village ofKendan. The goal of this strategy is to effectively and efficiently save time forvisitors who are unfamiliar with the new environment they are visiting, as well asto assist and facilitate them in getting clear and comfortable information. This studyemployed design methodologies, EGD methods, which included descriptive and matrixanalysis, as well as qualitative methods such data collecting through observations,interviews, and library studies. Keywords: environmental graphic design, signage, wayfinding, Nagreg Kendan Village, Tourist Village